Laparoscopic detorsion of isolated idiopathic fallopian tube torsion: conservative treatment in a 13-year-old girl - Ardıçlı, Burak; Ekinci, Saniye; Oğuz, Berna; Haliloğlu, Mithat; Tanyel, F. Cahit; Karnak, İbrahim (The Turkish Journal of Pediatrics, 2013)
Isolated fallopian tube torsion (IFTT) is a rare entity in adolescent girls. Invasive surgery, salpingectomy, was used during the initial surgery or at the time of recurrent torsion in 87% of previously reported cases. Herein, the authors present an adolescent premenarcheal girl with idiopathic IFTT, which was treated by laparoscopic detorsion, to emphasize that tubal torsion should be included in the list of differential diagnoses of abdominal pain in adolescent girls. Minimally invasive, organ-saving surgery should be done, and the child should be followed up for recurrent torsion.